Words substitute fists: Justifying punishment in a public good experiment - Christoph Engel; Lilia Zhurakhovska (Max Planck Institute for Research on Collective Goods, 2013)
Punishees regularly ask for justification. But is justification also effective? To answer this question under controlled conditions, we have conducted a public goods experiment with central punishment. The authority is neutral - she does not benefit from contributions to the public good. Punishment is costly. Along with the punishment decisions the authority writes justifications for her decisions. In the Baseline, authorities are requested to justify punishment decisions, but the reasons are kept confidential. In the Private treatment, the addressee is only informed about the justification of the authoritys decision affecting herself, not affecting others. In the Public treatment, all reasons are made public. Whenever reasons are communicated, there is less monetary punishment. Authorities partly substitute words for action. Contributions decay in later periods if the justification is only communicated to the addressee. In the remaining two treatments, contributions stabilize at a high level.
Keywords: H41; D63; C91; D62; D03; K14; 330; experiment; public Good; justification; authority; central intervention